Evaluation of Metabolic Parameters in Diabetic Patients With and Without Nephropathy - Ronuque Hussain, Saier Hussain, Arif Khan, Arbaj khan, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Diabetes mellitus (DM) is a chronic metabolic disorder characterized byhyperglycemia resulting from impaired insulin secretion, insulin action, or both. The interplaybetween glucose metabolism and lipid homeostasis plays a critical role in the onset and progressionof diabetic complications, particularly diabetic nephropathy